Printed Electronics: Inkjet Printed Bilayer Light‐Emitting Electrochemical Cells for Display and Lighting Applications (Small 20/2014). Issue 20 (October 2014) - Lindh, E. Mattias; Sandström, Andreas; Edman, Ludvig
<x xml:space="preserve">Abstract</x> On page 4148, L. Edman and co‐workers introduce an inkjet‐based, mask free, and additive patterning technique for light‐emitting electrochemical cells. The position and size of the pixels correspond directly to those of the inkjet‐deposited electrolyte droplets. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>